Pulsed Field Ablation for Pulmonary Vein Isolation in Atrial Fibrillation - Reddy, Vivek Y; Neuzil, Petr; Koruth, Jacob S; Petru, Jan; Funosako, Moritoshi; Cochet, Hubert; Sediva, Lucie; Chovanec, Milan; Dukkipati, Srinivas R; Jais, Pierre (Journal of the American College of Cardiology, 2019)
BACKGROUND: Catheter ablation of atrial fibrillation using thermal energies such as radiofrequency or cryothermy is associated with indiscriminate tissue destruction. During pulsed field ablation (PFA), subsecond electric fields create microscopic pores in cell membranes-a process called electroporation. Among cell types, cardiomyocytes have among the lowest thresholds to these fields, potentially permitting preferential myocardial ablation. OBJECTIVES: The purpose of these 2 trials was to determine whether PFA allows durable pulmonary vein (PV) isolation without damage to collateral structures. METHODS: Two trials were conducted to assess the safety and effectiveness of catheter-based PFA in paroxysmal atrial fibrillation. Ablation was performed using proprietary bipolar PFA waveforms: either monophasic with general anesthesia and paralytics to minimize muscle contraction, or biphasic with sedation because there was minimal muscular stimulation. No esophageal protection strategy was used. Invasive electrophysiological mapping was repeated after 3 months to assess the durability of PV isolation. RESULTS: In 81 patients, all PVs were acutely isolated by monophasic (n = 15) or biphasic (n = 66) PFA with ≤3 min elapsed delivery/patient, skin-to-skin procedure time of 92.2 ± 27.4 min, and fluoroscopy time of 13.1 ± 7.6 min. With successive waveform refinement, durability at 3 months improved from 18% to 100% of patients with all PVs isolated. Beyond 1 procedure-related pericardial tamponade, there were no additional primary adverse events over the 120-day median follow-up, including: stroke, phrenic nerve injury, PV stenosis, and esophageal injury. The 12-month Kaplan-Meier estimate of freedom from arrhythmia was 87.4 ± 5.6%. CONCLUSIONS: In first-in-human trials, PFA preferentially affected myocardial tissue, allowing facile ultra-rapid PV isolation with excellent durability and chronic safety. (IMPULSE: A Safety and Feasibility Study of the IOWA Approach Endocardial Ablation System to Treat Atrial Fibrillation; NCT03700385; and PEFCAT: A Safety and Feasibility Study of the FARAPULSE Endocardial Ablation System to Treat Paroxysmal Atrial Fibrillation; NCT03714178).
Keywords: Male; venae pulmonales; Treatment Outcome; lidé středního věku; Catheter Ablation; esophageal damage; Humans; Feasibility Studies; Middle Aged; senioři; mužské pohlaví; katetrizační ablace; Female; Aged; catheter ablation; pulsed field ablation; ženské pohlaví; electroporation; Pulmonary Veins; pulmonary vein isolation; fibrilace síní; lidé; Atrial Fibrillation; studie proveditelnosti; atrial fibrillation; výsledek terapie